Boko Haram : The History of an African Jihadist Movement - Thurston, Alexander (Book collections on Project MUSE., 2018)
"Drawing on sources in Arabic and Hausa, rare documents, propaganda videos, press reports, and interviews with experts in Nigeria, Cameroon, and Niger, Alexander Thurston sheds new light on Boko Haram's development. He shows that the group, far from being a simple or static terrorist organization, has evolved in its worldview and ideology in reaction to events. Chief among these has been Boko Haram's escalating war with the Nigerian state and civilian vigilantes. The book closely examines both the behavior and beliefs that are the keys to understanding Boko Haram. Putting the group's violence in the context of the complex religious and political environment of Nigeria and the Lake Chad region, the book examines how Boko Haram relates to states, politicians, Salafis, Sufis, Muslim civilians, and Christians. It also probes Boko Haram's international connections, including its loose former ties to al-Qaida and its 2015 pledge of allegiance to ISIS."--Publisher's description